(untitled) (Eurasian Research Bulletin, 2022)
The article analyzes the concept, essence and content of exemption from legal liability, the views of legal scholars and judicial practice from a scientific and theoretical point of view. The author of the article also puts forward his scientific interpretation of terms and concepts from the point of view of today’s legal practice in Uzbekistan.